Net Energy and Carbon Flow Analyses on four pathways for the utilization of Natural Gas as Automotive Fuel - Tan, Raymond Girard R; Culaba, B (ASEAN Journal of Chemical Engineering, 2004)
The development of the natural gas (NG) reserves ot the Philipines has led to interest in the use of NG as an automotive fuel. Successful utilation of NG as a fuel or motor vehicles will lessen the caunt dependence on imported petroleum whe reducing air emisions. particularly that of CO, which is the predominant cause of global climate change, energy analysis (NEA) and carbon flow analysis (CFA) were used to compare four dierent pathways for NG utilization: (a-b) direct use as fuel in liquified (LNG) or compressed (CNG) from; (c) conversion to methanol; and (d) convsion ta electncit for electric vehicle (EV) or hybrid electric vehicle (H)propusion. The assement was performed using fhe GREET 1 .5a fueI cycle inventory model to determine the best pactical environmental option (BPEO) among the our altematives. ModeI unceainties we dealt with using sensitivitas analysisl. When the analysis when based on 1 MJ of fuel energy delivered to the refueling site, CNG was the BPO, foow by the LNG, metanol, and elttricity pathways. Due to the variability ot fuel processing or conversion effectivities, the difference between LNG and methanoI was Found minimal. Basing the analys on 1km traveled by the end user vehicle, the differences in fueI economic of end user vehicles had a drastic effect on the assessment results. EIectricity was found to be the BPEO followed by metanol.CNG. and LNG. Establishing a definite ranking of the options, however was difficult due to the high degreeo of uncertainty in vehicle fueI economy projections.